2007
DOI: 10.1111/j.1600-6143.2007.01929.x
|View full text |Cite|
|
Sign up to set email alerts
|

Sirolimus‐Associated Infertility: Case Report and Literature Review of Possible Mechanisms

Abstract: The mammalian-target-of-rapamycin/mTOR-inhibitor sirolimus as a component of the immunosuppressive strategy after solid organ transplantation is effective at preventing allograft rejection. However, recent reports indicate that sirolimus is associated with altered sex hormone levels and impaired sperm quality parameters.Herein, we report on a case of sirolimus-associated infertility in a young male heart-lung transplant recipient and provide a detailed synopsis of potential mechanisms by which sirolimus may ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 29 publications
7
48
0
1
Order By: Relevance
“…It is not clear if this high prevalence is population-related, owing to ethnic and genetic predisposition, or if there is lack of reporting of this complication in the international literature. The metabolic and proteinuric complications of sirolimus seen in our patients are in line with the findings in the literature [14]. However, our observation that serum creatinine improved after sirolimus discontinuation suggests a nephrotoxic effect of sirolimius, contrary to what has been previously reported.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It is not clear if this high prevalence is population-related, owing to ethnic and genetic predisposition, or if there is lack of reporting of this complication in the international literature. The metabolic and proteinuric complications of sirolimus seen in our patients are in line with the findings in the literature [14]. However, our observation that serum creatinine improved after sirolimus discontinuation suggests a nephrotoxic effect of sirolimius, contrary to what has been previously reported.…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, the first case report of sirolimus-related infertility in a male renal transplant patient was reported by Bererhi et al in 2003 [11]. One case of oligospermia in a male heart-lung transplant patient and another case of azoospermia in a male renal transplant were reported [14,15]. The prevalence as well as the clinical impact of sirolimus-related gonadal suppression was not documented in the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 84%
“…Following kidney transplant, women treated with long-term sirolimus (13 mo or longer) developed amenorrhea, which resolved with its discontinuation, and men who were azoospermic developed normal semen parameters and fathered children following discontinuation (46). Case reports describe temporary azoospermia in men treated with sirolimus, which resolved after its discontinuation or switch to a different agent, and a rodent study further demonstrated the reversible impact of sirolimus on male fertility (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In general, men have normal testosterone after transplant (200), but sirolimus, in particular, has been reported to reduce sperm count and in some cases alter gonadotropins, as well as reduce fertility rates (202,203). It is currently unknown whether a male transplant recipient on immunosuppression can confer any other risk to a child that is conceived.…”
Section: Eye Care Foot Care Preventing Infections and Reproductmentioning
confidence: 99%